Novel elastomer dye-functionalised POSS nanocomposites: Enhanced colourimetric, thermomechanical and thermal properties - R. A. Shanks; S. Spoljaric (eXPRESS Polymer Letters)
Nanocomposites consisting of poly(styrene-b-butadiene-b-styrene) (SBS) and polyhedral oligomeric silsesquioxanes (POSS) were prepared using a solvent dispersion method. POSS molecules were functionalised with two dichlorotriazine reactive dyes (CI Reactive Blue 4, CI Reactive Red 2) prior to compounding. Infrared spectroscopy confirmed functionalisation.Scanning electron microscopy revealed an increase in filler aggregation with concentration, with preferential phase selectivity. Ultraviolet spectroscopy and colourimetry confirmed colour uniformity and suggested that colour intensity could be controlled. Functionalised POSS improved thermal stability by imparting restrictions on SBS chain motions. Tensile stress-strain analysis revealed an increase in modulus with filler concentration, while creep deformation decreased and permanent strain increased with POSS content. Storage modulus, loss modulus and glass transition temperature increased with filler content due to effective SBS-POSS interaction. Nanocomposite properties were influenced by the phase the filler was dispersed throughout and the structure of the dye chromophore.